Outcome of combination of methods of educational interventions in physiology for first-year MBBS students - Bhattacharya, Srabani; Wagh, Rucha; Kartikeyan, Sundaram; Malgaonkar, Aniruddha A.; Khadse, Sandhya S. (International Journal of Research in Medical Sciences, 2019)
Background: This comparative, before and after study (without controls) was conducted in a municipal medical college to compare the cognitive domain scores obtained by first-year MBBS students after didactic lectures with that obtained after an educational intervention that combined integrated teaching with clinical scenarios. Methods: After obtaining prior permissions, the purpose of the study was explained to first-year MBBS students and written informed consent was obtained. After attending curriculum-based didactic lectures on the alimentary system, the students (n=62, females: n=29, 46.77% and males: n=33, 53.23%) took a pre-test comprising ten questions (total 20 marks). After the pre-test, the participants attended an educational intervention that combined integrated teaching with clinical scenarios on the same topic. Subsequently, the post-test was administered using a questionnaire that was identical to that of the pre-test. Results: The mean overall marks obtained in the pre-test was 14.73±1.87 (95% CI: 14.26-15.19), while that obtained in the post-test was 17.16±1.73 (95% CI: 16.73-17.59), exhibiting highly significant (p <0.00001) difference. The gender difference in scores was significant (p=0.011) for only question no. 1 in the pre-test and there was no significant gender difference in the post-test. Conclusions: A combined method of educational intervention was found to enhance the cognitive domain scores of students. Though a larger study would be needed to generalize the findings, male students seem to need an additional educational intervention to improve their cognitive domain scores. Despite time limitations in the teaching schedule for the first-year MBBS course, integrated teaching with case scenarios can be implemented to impart early clinical exposure.